Engineering Hierarchical CoO Nanospheres Wrapped by Graphene via Controllable Sulfur Doping for Superior Li Ion Storage. Issue 42 (29th September 2020) - Hu, Yifan; Li, Zichuang; Hu, Zhongchao; Wang, Liang; Ma, Ruguang; Wang, Jiacheng
Abstract: The inferior conductivity and large volume expansion impair the widespread applications of metal oxide‐based anode materials for lithium‐ion batteries. To address these issues, herein an efficient strategy of structural engineering is proposed to improve lithium storage performance of hierarchical CoO nanospheres wrapped by graphene via controllable S‐doping (CoOS0.1   @ G). S‐doping promotes the Li + diffusion kinetics of CoO by expanding the interplanar spacing of CoO, lowering the activation energy, and improving the pseudocapacitance contribution. Meanwhile, the electronic structure of CoO is adjusted by S‐doping as confirmed by density functional theory calculations, thus enhancing the conductivity. Finite element analysis reveals that the produced Li2 S during lithiation improves the structural stability of the S‐doped electrode, which is further confirmed by experimental observation. As expected, CoOS0.1   @ G exhibits excellent lithium storage performance with an initial discharge capacity of 1974 mAh g −1 at 100 mA g −1, and high discharge capacity of 1573 mAh g −1 after 400 cycles at 500 mA g −1 . It is believed that the insights into the structural doping enlighten research to explore other metal oxides for fast and stable Li ion storage. Abstract : Hierarchical sulfur‐doped CoO nanospheres wrapped by graphene (CoOS0.1   @ G) deliver a high discharge capacity (1974 mAh g −1 ), excellent rate capability (635.8 mAh g −1 at 5000 mA g −1 ), and remarkable cycling stability (1573 mAh g −1 after 400 cycles at 500 mA g −1 ), which are credited to the modulation of electronic structure, reaction kinetics, and electrode integrity by precise sulfur doping.